DEVELOPMENT OF A STRETCHABLE CONDUCTIVE SENSOR FOR FLEXIBLE DEFORMATION: A PRELIMINARY STUDY - Mohd Mustapha, Nurul Hasyimah; Muhammad Razif, Muhammad Rusydi; Nasir, Siti Hana; Mohd Nordin, Ili Najaa Aimi; Yong Tze Mi, Yong Tze Mi (2023)
This research presents preliminary characterization studies for a stretchable conductive sensor. It was developed specifically to detect strain changes that occur including flex changes. Some issues in conventional strain measurement are found to be less suitable due to the inaccuracy to measure the strain for an elongation using a flexible curve ruler, especially strain related to angle changes. Therefore, a study on the development of a stretchable conductive sensor is required. This initial study will focus on characterizing the suitability of fabric materials and thread patterns to develop a sensor that will be used to measure stretch more accurately. In this study, conductive yarns were constructed with two types of stretchable fabrics having different percentages of spandex elements. The thread will be sewn to the side of the fabric in two of the fabric states, namely course (horizontal) and wales (vertical). Forboth conditions, five (5) similar samples were sewn for 8% and 15% spandex fabric. Preliminary results found that the best sensor performance was a fabric containing 15% spandex material with conductive threads sewn along the horizontal orientation of the fabric. In a study on resistance varying with the tension applied to the sensor, model D showed the best performance when stretched up to a force of 4 N. The resistance shown by the sensor varies from 47MΩ to 66MΩ relative to the applied force from 0 N to 4 N. The results of this preliminary study are expected to be used in widespread measurement applications.